Kekuatan Komunitas Lokal Sebagai Pilar Masyarakat Sipil - Erfain Erfain (FKIP UNSULTRA, 2025)
Local communities play a strategic role as pillars of civil society, capable of driving social change, strengthening solidarity, and maintaining the sustainability of local culture and wisdom. This literature review aims to examine how the strength of local communities forms the foundation of civil society within a social, political, economic, and cultural context. The method used was a literature review of scientific articles, books, and research reports published between 2018 and 2025. The study's findings indicate that local communities function as spaces for democratic participation that strengthen social cohesion, reduce inequality, and increase community resilience in the face of crises. Furthermore, local wisdom, passed down from generation to generation, has proven to be a crucial instrument in maintaining social harmony and environmental sustainability. However, the challenges of modernization, globalization, and the penetration of digital technology often erode the value of collectivity, the primary strength of local communities. Therefore, community empowerment strategies based on active participation, multi-stakeholder collaboration, and the revitalization of local wisdom are needed to ensure communities remain adaptive in the face of changing times. This literature review confirms that the strength of local communities is a crucial foundation for realizing an inclusive, resilient, and sustainable civil society in Indonesia.